The Impact of Financial Regulation on the Development of Distributed Ledger Technology (DLT) Firms - Hashimy, Loha; Sandner, Philipp (Frontiers in Blockchain, 2020)
There is disagreement in the literature concerning the impact of regulations on firms’ development. While some researchers believe that regulation impedes companies’ development (Jalilian et al., 2007; Poel et al., 2014), others argue that regulations enable companies’ development (Mayson et al., 2014; Peck et al., 2018). This paper aims to contribute to a better understanding of the impact of financial regulations on development of token-based Distributed Ledger Technology (DLT) firms. In-depth semi-structured open-ended interviews have been conducted with 20 DLT firms in Europe during April and May 2019. Our results show that the impact of financial regulation can be ambiguous as it can both enable and constrain a firm’s development.